Pharmacotherapeutic Potential of Natural Products in Neurological Disorders - Saroya, Amritpal Singh (Springer Singapore, 2018)
Natural Products have always played a pivotal role as sources for drug lead compounds. This book is aimed at providing inside purview of the scope of natural products (including herbal and marine) in the possible treatment of neurological disorders. The book explains pre-clinical neuropharmacological investigations done on herbs including Bacopa monnieri, Hypericum perforatum, Passiflora incarnata, Scutellaria baicalensis and Piper methysticum. It provides a comprehensive overview of the role of phytoconstituents like huperzine, curcumin, Salvinorin A, bioflavonoids, sulforaphane, tanshinone IIA, tetramethylpyrazine, tetrahydrocannabinol, and cannabidiol in the treatment of neurological disorders. The book provides a modern concept of herbal medications, neuropharmacology of marine bioactive products and Ayurvedic formulations, herbal drugs with abuse potential and neurotoxic mycotoxins.